Siemensadon ennustemallit männylle ja kuuselle - Pukkala, Timo; Hokkanen, Tatu; Nikkanen, Teijo (Metsäntutkimuslaitos, 2011)
Seloste artikkelista Prediction models for the annual seed crop of Picea abies (L.) Karst. (Norway spruce) and Pinus sylvestris L. (Scots pine) in Finland. Silva Fennica 44(4): 629–642.
Tutkimusseloste